2021
DOI: 10.1159/000514075
|View full text |Cite
|
Sign up to set email alerts
|

Serum Vitamins and Homocysteine Levels in Obsessive-Compulsive Disorder: A Systematic Review and Meta-Analysis

Abstract: Vitamin and homocysteine (Hcy) alternations have been associated with psychiatric disorders. The aim of this meta-analysis was to assess the association of serum vitamin and Hcy levels with obsessive-compulsive disorder (OCD). Following PRISMA protocol, we used the databases including Scopus, PubMed, Google Scholar, and Web of Science with no time restriction. Data were pooled using a random-effects model and/or fixed-effects model to estimate the standard mean difference (SMD) for evaluation of the strength o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 71 publications
1
11
4
Order By: Relevance
“…Some case control studies (33)(34)(35)(36)(37)(38)(39)(40) and a meta-analysis (41) concentrated on the relationship between OCD and MDA. In contrast with our study, Ranjekar et al observed no signi cant differences in serum levels of lipid peroxidation markers between patients with schizophrenic and healthy control (42) A meta-analysis found an inverse association between vitamin E blood levels and OCD (44). In the present study, serum GSH and TAC levels were not signi cantly different between two groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Some case control studies (33)(34)(35)(36)(37)(38)(39)(40) and a meta-analysis (41) concentrated on the relationship between OCD and MDA. In contrast with our study, Ranjekar et al observed no signi cant differences in serum levels of lipid peroxidation markers between patients with schizophrenic and healthy control (42) A meta-analysis found an inverse association between vitamin E blood levels and OCD (44). In the present study, serum GSH and TAC levels were not signi cantly different between two groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, Ersan et al (34) and Shohag et al (35) observed a signi cant decreased level of vitamin E in serum of OCD patients, but Shohag et al did not observe any signi cant difference regarding serum vitamin A levels between OCD and healthy controls. A meta-analysis found an inverse association between vitamin E blood levels and OCD (44). In the present study, serum GSH and TAC levels were not signi cantly different between two groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Our patients with vitamin D and folic acid deficiencies were offered substitution therapy. A noteworthy reduction in vitamin B12 levels as reported in a meta-analysis [57] was not observed in this patient cohort.…”
Section: Probable and Possible Organic Ocd Casescontrasting
confidence: 44%
“…Reduced vitamin D levels have been described in children with OCD [54] or PANDAS [55], although more recent studies have found no significant differences in children with OCD [56]. In a recent meta-analysis of these studies, no association was found between OCD and vitamin D deficiency [57]. Nevertheless, vitamin D may have a disease-modifying effect on OCD [58].…”
Section: Probable and Possible Organic Ocd Casesmentioning
confidence: 96%